(untitled) (Historias, 2004)
History of everyday life, as an specific approach model with its own contents, concepts and methodology, constitutes a relatively recent development within Argentine historyography. The objective of this work is to make a critic revision and balance of the contributions that, within the framework of this tendency to study everyday issues, have studied some specific actors in a particular space and time: the popular classes in the city of Buenos Aires at the end of the 19th century and the beginning of the 20th century. The aim is to identify which are the issues that have get the attention of the authors and which are the analytic viewpoints that they have taken.